1982
DOI: 10.1007/bf02019937
|View full text |Cite
|
Sign up to set email alerts
|

Combination effect of azthreonam with four aminoglycosides on nosocomial gram-positive cocci and non-fermenting gram-negative bacteria

Abstract: The inhibitory combination effect of azthreonam with gentamicin, tobramycin, amikacin and netilmicin respectively against 50 non-fermenting gram-negative rods and 30 gram-positive cocci was compared using the checkerboard agar dilution technique. On average 49.5% of all non-fermenting strains were inhibited by additive, and 48.5% by synergistic azthreonam-aminoglycoside combinations, but only 4.5% of the gram-positive cocci were inhibited by synergistic combinations. No antagonism occurred. No significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Recent years have witnessed a resurgence of interest in enterococci and studies have shown the increasing rate of hospital-acquired enterococcal infections [6,7]. Enterococci are intrinsically tolerant to antibiotics that inhibit cell wall synthesis, such as penicillin, vancomycin, and imipenem, but are killed by the synergistic action of these antibiotics in combination with an aminoglycoside [8]. However, there is no synergy when the enterococcal strain has high-level resistance (MIC > 2,000 mg/1) to the aminoglycoside [9].…”
Section: Discussionmentioning
confidence: 99%
“…Recent years have witnessed a resurgence of interest in enterococci and studies have shown the increasing rate of hospital-acquired enterococcal infections [6,7]. Enterococci are intrinsically tolerant to antibiotics that inhibit cell wall synthesis, such as penicillin, vancomycin, and imipenem, but are killed by the synergistic action of these antibiotics in combination with an aminoglycoside [8]. However, there is no synergy when the enterococcal strain has high-level resistance (MIC > 2,000 mg/1) to the aminoglycoside [9].…”
Section: Discussionmentioning
confidence: 99%